Salivary Proteome In Periodontal Diagnosis - DHIRAJ TRIVEDI,; CHHAYA TRIVEDI, (International Journal of Pharma and Bio Sciences, 2012)
Periodontitis is a chronic bacterial infection to gingival tissue leading to inflammation, degeneration of connective tissue or increased bone turn over. Apart from clinical examination, analysis of GCF is a good diagnostic tool but, has several limitations. Components of salivary proteome, enzymes, are gaining importance in clinical diagnosis because of non-invasive, simple and less demanding procedures. Aim of our present study is to estimate LDH, AST, ALP and CPK enzymes in unstimulated saliva for valuing their importance as routine screening tool in diagnosis of Periodontitis. In our study we conclude that increased activity of enzymes like LDH, AST, and ALP in whole unstimulated saliva when compared with normal control provides good insight of Periodontitis. Estimations are simple, convenient and do not need any expert examiner, it can be adapted as test for screening Periodontitis in public health.